La azoxistrobina induce aberraciones cromosómicas en raíces de la hidrófita Bidens laevis L. - Pérez, Débora Jesabel; Menone, Mirta Luján; Tognetti, Jorge; Lukaszewicz, Germán (Centro de Ciencias de la Atmosfera, UNAM, 2021)
Aquatic plants can be used as in situ bioindicators of water quality due to their ability to accumulate agrochemicals. However, these plants may be at significant ecotoxicological risk from pesticides applied in crop fields. The fungicide azoxystrobin (AZX) induces DNA damage and changes in the antioxidant enzymatic system in leaves of the submerged hydrophyte Myriophyllum quitense. In the present study, the objectives were to determine whether AZX induces chromosomal damage in roots of the wetland plant Bidens laevis and to evaluate whether the damage in the antioxidant system was associated with damage in the photosynthetic system. Two experiments were carried out to evaluate the short-term effects (1 or 2 days) of the exposure to different concentrations of the active ingredient of AZX (0, 0.1, 1, 10, 50, 100 μg/L) on intact B. laevis plants. In the first experiment, photosynthetic biomarkers, including chlorophyll a fluorescence, SPAD units, and chlorophyll a and b content, were measured. In the second experiment, the frequency of chromosome aberrations (CA) was evaluated in root tips. In general, the photosynthetic biomarkers evaluated were not affected by AZX, except for a decrease in chlorophyll b content at 100 μg/L. Total CA increased at all AZX concentrations and the most frequent abnormalities were laggards and chromosomes not congregated at the metaphase equator, both indicators of spindle disturbance. This is the first report of AZX-induced chromosomal aberrations in a wetland plant exposed to environmentally relevant concentrations of the fungicide. The reason why AZX exposure had only a limited impact on biomarkers of the photosynthetic apparatus is discussed.